(3JaSjQ BjI GdONGf (B( (3Ke ESJhi Edi GdSeGA hgi ONGf (B)s - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje (B( (3Ke GSJhi Edi GdSeGA hgj ONGf (B) (3CTGQ HGdONGf Edi eGOI GdSeGA aGdONGf Lh ef XdeGA ai efHY GdXdeI ef MjK GfgG efHY GdYOe s
(3BNQgG (B:s
(3GdMGedI ddchGcH GdSHYI hgj SHYI hGdjheGf NHQ ESekG jYfi GdeGOI hGdUhQI bhdg JYGdi (B( (3hChMi ai cd SeGA CeQgG (B) (3ETGQI Edi GdYbhd GdeaGQbI GdJi gi eMQcGJgG Ydi SHjd GdJThjb hGdJYTjb s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(423(8)) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs